Factores que favorecen el cambio en el comportamiento de lavado de manos, manejo de agua en el hogar y uso de mantenimiento de la letrina en las familias de 9 caseríos del distrito de Baños del Inca - Alvarado Abanto, Olga Beatriz (2017)
Background: there is little research on the aspects that favor the change in health behavior in the rural population, therefore, knowing them from the perception of the families will contribute to improving the sustainability and impact of health education programs and rural sanitation projects. Objective: To identify the aspects that, from the perception of the participants, favor the behaviors of hand washing, water management in the home, and use and maintenance of the latrine in the families of the district of Baños del Inca, province of Cajamarca. Material and Method: study of perceptions, descriptive of qualitative-quantitative, cross-sectional design. The target population was made up of 71 families residing in hamlets classified at risk by the health establishments of the Ministry of Health. For data collection, semi-structured questionnaires, interviews and direct observation were applied. Results: it was found that 85% of surveyed families perceived changes in health behavior. Regarding the aspects that favored behavior change: 42.3% refer to access to resources; 30% attribute to the information and positive opinions of close people, authorities or leaders of their community and 86% to the support and accompaniment of health personnel. Conclusions: it was evidenced the existence of aspects related to the external and internal environment of the families that favor the implementation of the behaviors in the rural population.